The Impact of Mathematics Learning Using A STEM-PJBL Based Ethnomathematics Approach on Students' Creative Mathematical Thinking - Aprillia Sabrina, Herra; Purbarini Kawuryan, Sekar; Sri Hasturi, Woro; Muhamad Firdaus, Fery; Razali, Fazilah; Mauluah, Luluk (Universitas Pendidikan Ganesha, 2025)
The problem underlying this research is the low level of students' creative mathematical thinking skills, which is still challenging in the mathematics learning process. Conventional learning approaches that are less contextual are often unable to stimulate creativity and innovative problem solving. This study aims to improve students' ability to think creatively in elementary school teacher education. The study subjects were second-semester students at a university in Yogyakarta. Data collection used a mathematical, creative thinking test as an instrument. The quasi-experimental method was chosen for quantitative research in this study with an unequal control group design because it was experimental, and the sample determination was not carried out randomly. Instead, it used a deliberate sampling technique on second-semester students of the elementary madrasah teacher education undergraduate program. In the test, the increase and effect of the treatment were observed as measured using the n-gain value. The study results showed that the ability to think creatively in mathematics of students in the experimental class exceeded the average score of the control class. It can be concluded that ethnomathematics-based PjBL-STEM effectively improves students' problem-solving ability in mathematics. The implementation of ethnomathematics-based STEM-PjBL is important to be used as a mathematics learning strategy by integrating local cultural elements to provide a more meaningful learning experience at the student level. The implications of this study can be used as a reference by educational policymakers in compiling a curriculum that encourages strengthening 21st-century skills.